Pre-Columbian agriculture, fire, and Spanish contact: A 4200-year record from Laguna Los Mangos, Costa Rica. (November 2019) - Johanson, Erik N; Horn, Sally P; Lane, Chad S
We present a lake-sediment record of pre-Columbian agriculture and fire history from the lowlands of southern Pacific Costa Rica that captures the arrival of maize agriculture at ca. 3360 cal yr BP in the Diquís subregion of the Gran Chiriquí archeological region. Our 4200-year record from Laguna Los Mangos begins 1000 to 2000 years earlier than other lake records from the region and provides the first microfossil and geochemical evidence of vegetation and fire prior to the establishment of maize agriculture. This early portion of the record shows evidence of fire events associated with land clearance or field preparation and maintenance for subsistence activities. Alternatively, these were wildfires ignited unintentionally by people or naturally by lightning or volcanism. Evidence of early maize by ca. 3200 cal yr BP was found at Laguna Zoncho in the southeastern section of the Diquís subregion. Our discovery of early maize agriculture at ca. 3360 cal yr BP in the Laguna Los Mangos watershed in the northwestern portion of the Diquís subregion indicates a rapid adoption of maize agriculture in the region after initial introduction. Pre-Columbian agriculture and fire activity at Los Mangos is nearly continual until historic times, but with a decline after ca. 1170 cal yr BP, coincident with the early Terminal Classic Drought (TCD). We infer a pronounced drying of the lowland environment at Laguna Los Mangos based on a depositional hiatus in the record at ca. 950 during late TCD. Agricultural proxies indicate reduced watershed activity during the 'Little Ice Age' following Spanish contact in southern Central America until the 20th century.